APPLICATION OF PRODUCT QUALITY ASSURANCE IN MANUFACTURE, CASE STUDY IN MECHANICAL ENGINEERING DEPARTMENT, SRIWIJAYA UNIVERSITY - Amrillah Nugrasyah; Amrifan Saladin Mohruni (Universitas Sriwijaya, 2019)
Product Quality Assurance (PQA) is a standard procedure to ensure the product quality in practical manufacturing engineering. In this study the PQA-procedure will be applied for academic assurance in Mechanical Engineering Department, Sriwijaya University. The objective of this study is to generate web based Academic Quality Assurance (AQA) in the Department, which accomplices with National Accreditation Agency for Higher Education (BAN-PT). The development of web based AQA was carried out using an open source PHP, MySQL, CSS and REST API to ensure the web integration with the existing website of Sriwijaya University. The results show that this application can overcome the existing problems when the Academic Quality Assurance was conducted manually. The AQA web can work smoothly